Utilization of Colonial Heritage Learning Resources in Locality-Based Senior High School - Ulul Fikriyani; Totok Hari Prasetiyo; Mahfud, Mahfud (CV. Sekawan Siji, 2024)
District Tegaldlimo is a district that is located in South Banyuwangi which are named Alas Purwo National Park in Java language which is defined as